Nemzeti érzelmek és a kisebbségek iránti attitűdök a mai Magyarországon - Kelemen, Ágnes (Szociológiai Szemle, 2024)
The present study focuses on issues related to the concept of the nation and how its minorities are represented in the attitude structure of individuals. The research examined the structure o f attitudes, organized around the notion of the nation, and explored the structural relationship between national sentiments and attitudes towards cohabitant minority groups connected to the concept of nation. We have investigated the attitudes organized around the notion of the nation, attitudes toward the Romany and the Jewish minorities in Hungary and explored the structural relationship between the two clusters of dispositions. The investigation tested three hypotheses set up concerning the assumed relations by a questionnaire survey conducted on a non-representative sample of secondary school students in Budapest. The data yielded by our survey provided a firm base for two of the hypotheses while a third one had been disproved. We could prove that the representational structure of the attitudes towards minorities are indeed organized as three main clusters or strategies: assimilation, discrimination and tolerance. We tested the validity of the Dekker-Malova Nationalism Model in Hungary and proved the systematic relationship between stages of national orientations and attitudinal strategies towards minorities. However, we had to refute the hypotheses regarding the existence of one dominant strategy towards minorities as such, regardless of the actual group in question.